Bradycardia and slowing of the atrioventricular conduction in mice lacking Ca(V)3.1/alpha(1G) T-type calcium channels - Mangoni, ME; Traboulsie, A; Leoni, AL; Couette, B; Marger, L; Le Quang, K; Kupfer, E; Cohen-Solal, A; Vilar, J; Shin, HS; Escande, D; Charpentier, F; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2006)
The generation of the mammalian heartbeat is a complex and vital function requiring multiple and coordinated ionic channel activities. The functional role of low-voltage activated (LVA) T-type calcium channels in the pacemaker activity of the sinoatrial node (SAN) is, to date, unresolved. Here we show that disruption of the gene coding for Ca(v)3.1/alpha(1G) T-type calcium channels (cacna1g) abolishes T-type calcium current (I-Ca,I-T) in isolated cells from the SAN and the atrioventricular node without affecting the L-type Ca2+ current (I-Ca,I-L). By using telemetric electrocardiograms on unrestrained mice and intracardiac recordings, we find that cacna1g inactivation causes bradycardia and delays atrioventricular conduction without affecting the excitability of the right atrium. Consistently, no I-Ca,I-T was detected in right atrium myocytes in both wild- type and Ca(v)3.1(-/-) mice. Furthermore, inactivation of cacna1g significantly slowed the intrinsic in vivo heart rate, prolonged the SAN recovery time, and slowed pacemaker activity of individual SAN cells through a reduction of the slope of the diastolic depolarization. Our results demonstrate that Ca(v)3.1/T-type Ca2(+) channels contribute to SAN pacemaker activity and atrioventricular conduction.
Keywords: SINOATRIAL NODE; PACEMAKER ACTIVITY; CA2+ RELEASE; TARGETED DISRUPTION; SODIUM-CHANNELS; FUNNY CURRENT; GENE SCN5A; CELLS; HEART; REQUIREMENT